Microplastics in the Mediterranean Sea: Sources, Pollution Intensity, Sea Health, and Regulatory Policies - Sharma, Shivika; Sharma, Vikas; Chatterjee, Subhankar (Frontiers in Marine Science, 2021)
Microplastic pollution is one of the emerging threats across the globe and is becoming a topic of intense study for environmental researchers. At present, almost all of the world’s oceans and seas are contaminated with microplastics but the Mediterranean Sea has been recognized as a target hotspot of the world as the microplastic concentration in this region is approximately four times greater than the North Pacific Ocean. Because of the distinguishing semi-enclosed morphology of the Mediterranean Sea, and different plastic waste generating activities originating from surrounding countries the Mediterranean Sea is highly vulnerable to microplastic pollution. Different plastic families have been reported in the Mediterranean Sea and the Physico-chemical features of these plastic polymers play an important role in the interactions between these plastic particles and other organic matter in the water bodies. The ingestion of microplastics by marine animals is an issue of concern as microplastic acts as vectors for other harmful pollutants adsorbed onto their surface. This review provides a detailed discussion on the persistence of microplastics in the Mediterranean Sea that have been identified in surface water and also in sediments and deep sea-floor. Various sources of these synthetic materials and the intensity of low and high-density polymers pollution in the Mediterranean Sea have also been discussed. This review also focuses on the threatened species in the Mediterranean Sea and the fate of the plastisphere community in its ecosystem. In the end, we highlight a series of important regulations and policies adopted by Mediterranean countries to control and manage the microplastic pollution in this region.